(untitled) (Archaeologia Adriatica, 2011)
The development of towns during the transition from Classical Antiquity to the Early Middle Ages is the least known stage in the entire poleogenesis process on the territory of Croatia. Although Croatian Classical archaeology has researched a number of significant towns, there are still no completely excavated urban settlements. This makes the study of the early mediaeval stage of towns with a Classical Antiquity nucleus and the transmission of the Classical Antiquity urban tradition into the Middle Ages rather difficult. The paper gives a historical overview of campaigns significant in understanding the poleogenesis of selected towns.